Dispersive Liquid-Liquid Microextraction Combined with Ultrahigh Performance Liquid Chromatography/Tandem Mass Spectrometry for Determination of Organophosphate Esters in Aqueous Samples - Haiying Luo; Yanping Xian; Xindong Guo; Donghui Luo; Yuluan Wu; Yujing Lu; Bao Yang (The Scientific World Journal)
A new technique was established to identify eight organophosphate esters (OPEs) in this work. It utilised dispersive liquid-liquid microextraction in combination with ultrahigh performance liquid chromatography/tandem mass spectrometry. The type and volume of extraction solvents, dispersion agent, and amount of NaCl were optimized. The target analytes were detected in the range of 1.0–200 µg/L with correlation coefficients ranging from 0.9982 to 0.9998, and the detection limits of the analytes were ranged from 0.02 to 0.07 µg/L (S/N=3). The feasibility of this method was demonstrated by identifying OPEs in aqueous samples that exhibited spiked recoveries, which ranged between 48.7% and 58.3% for triethyl phosphate (TEP) as well as between 85.9% and 113% for the other OPEs. The precision was ranged from 3.2% to 9.3% (n=6), and the interprecision was ranged from 2.6% to 12.3% (n=5). Only 2 of the 12 selected samples were tested to be positive for OPEs, and the total concentrations of OPEs in them were 1.1 and 1.6 µg/L, respectively. This method was confirmed to be simple, fast, and accurate for identifying OPEs in aqueous samples.